"Latvia a decade out from the world's largest GDP crash: how it collapsed and how to improve its economic performance". (2nd January 2021) - Sommers, Jeffrey; Briskens, Kaspars
ABSTRACT: This article enumerates several sectors where Latvia's economic performance can be enhanced. Yet, it also delivers by way of a long introduction an overview of Latvia's economic development in the post-Soviet period from a heterodox perspective that hints at why good options might not have been selected in the past. Following the above overview, we provide a detailed sectoral analysis of Latvia's economy since the 2008 financial shock that reveals continued hindrances to its development. We conclude by outlining development-friendly tax and industrial policy recommendations to promote Latvia's continued transformation into a more modern, sustainable, socially responsible and digitally enabled economy.